No-fault compensation scheme for obstetric injuries: a viable alternative? - Mohd Najid, Khadijah; Jahn Kassim, Puteri Nemie (LexisNexis, 2016)
Obstetric injuries, especially neurological impairment involving damage to the brain such as cerebral palsy or mental retardation is often considered as the most tragic of all obstetric outcomes, as it usually results in permanent disabilities and malformations. The lifelong damage not only denies the victims of physical freedom, but also poses significant psychosocial and emotional challenges to the inflicted children and their families. Obstetric injuries which occur in the early years of the victim’s life prejudice the victim’s quality of life by depriving the victim of ‘years of enjoyment, independence and productivity, and imposing years of suffering, debility and dependency’.Caring for a child inflicted with obstetric injury also involves a huge economic commitment, as they require comprehensive medical rehabilitation and lifelong assistance and care. The expensive cost turns out to be a substantial burden on the family where majority of affected families find difficulty in making financial ends meet, and consequently this burden becomes detrimental to both their physical and psychological well-being.3 This often triggers the search for substandard care on the part of the medical provider in charge to have them assume part of the cost,4 and malpractice litigation is seen as a platform for justification and to some extent alleviates the emotional pain associated with the incident.